New Orleans as the city of misfit women in Jezebel (William Wyler, 1938) and The Flame of New Orleans (René Clair, 1941) - Taïna TUHKUNEN (E-REA)
In several Hollywood movies on the antebellum South, the city of New Orleans pivots upon an unruly woman, ill-adapted to the codes and customs of the country, to serve the cinematographic portrayal of the 19th century Louisiana city, viewed as a topos of cultural and sexual instabilities, as well as a perfect site for spectacles and shows of all kinds. Viewed as a strikingly un-American city where cultural codes mingle and mix without, however, engendering a “melting pot”, New Orleans offers an engaging backdrop for filmic fictions challenging the archetypal romantic image of the “Old South”.This article explores two such fictional female figures who defy the vision of the pastoral South rooted in 19th century plantation novels in William Wyler’s Jezebel (1938) and The Flame of New Orleans (1941), a movie made by the French filmmaker René Clair during his exile in the United States during the Second World War. In the former, a Southern Belle named Julie Marsden (Bette Davis) transgresses the Southern honor codes, while René Clair foregrounds a dubious French Countess, Claire Ledoux (Marlene Dietrich) whose arrival disturbs the gentry of the famous harbor city. To what extent the leading lady’s emblematic misconduct ultimately triggers the greatest cataclysm in the South before the Civil War (1861-1865)—the outbreak of yellow fever that devastated New Orleans in the 1850s—remains a question mark at the end of Wyler’s melodrama, leading the spectator to ponder over the connections between the calamitous conduct of the female misfit and the mishaps and calamities befalling upon the in/famous Southern city. More humorously, yet resonating with the iconoclasm of William Wyler’s rebellious neworleansian heroine, René Clair’s satirical film presents us with a Southern city which it not to be confused with Atlanta, Georgia, in these two films representative of the “southern genre”.